RISK MANAGEMENT IN ROBUSTA COFFEE SUPPLY CHAIN (CASE STUDY IN GUNUNG SUSURU FARMERS GROUP, KADUWULUNG VILLAGE, SITURAJA DISTRICT, SUMEDANG REGENCY, WEST JAVA) - Nur Aisyah, Fitria
Sumedang Regency is one of the Robusta coffee-producing districts in West Java. This thesis takes a case study on the Gunung Susuru Farmers Group, Kaduwulung Village, Situraja District, Sumedang Regency. The group that produces a coffee brand is called Kopi Kadiran. This study aims to identify the types of risks in the Kadiran coffee supply chain, assess the risks in each Kadiran coffee supply chain actor, and determine risk mitigation strategies in the Kadiran coffee supply chain. The method used for the analysis of supply chain identification of Kadiran coffee is carried out using the APO (Asian Productivity Organization) approach, then the risk identification analysis uses the SCOR (approachSupply Chain Operation References) and the risk assessment is analyzed using the FMEA (methodFailure Mode and Effects Analysis). The results of the risk assessment are risk priorities which are assessed based on the level of severity, occurrence and detection so that the RPN (value is generatedRisk Priority Number). Followed by the AHP (methodAnalytical Hierarchy Process)to find risk mitigation strategies in the robusta coffee supply chain. Based on the results of the study, 11 risks were obtained for each actor of the Kadiran coffee supply chain. The result of the highest risk faced by processing farmer actors is limited production capacity with a value of RPN 192, the highest risk faced by distributor actors is competition between products with a value of RPN 210, and the highest risk faced by coffee shop actors is consumer purchasing power decreases with a value of RPN 168 Based on the results of the AHP calculation, the weight of the interest of the processing farmer obtained the highest value of 0.482, which means that the actor plays an important role in the Kadiran coffee supply chain. The strategy in mitigating these risks is the integrated application of SOP and GAP procedures (0.451) for processing farmer actors, establishing an integrated marketing system (0.495) for distributor actors and intensifying sales promotions on social media and marketplaces (0.688) for coffee shop actors. This strategy is considered the most appropriate strategy to mitigate risks in the robusta coffee supply chain.